Adaptation Strategies of Grobogan Regency Farmers in Face of Climate Change. Issue 1 (1st October 2022) - Esariti, L; Nida, R S; Handayani, W; Rudiarto, I
Abstract: The advent of climate change in Grobogan Regency is marked by the lengthy dry season, prevalence of rat attacks and changes in the growing season due to weather instability. This article aims to explore adaptation strategies for farmers in dealing with the problem of declining crop productivity due to climate change. Based on observations, expert interviews, and questionnaires delivered to the population, it was concluded that the strategies implemented among the farmers were aimed at maintaining livelihoods. The survey results indicated that there were different agricultural patterns in the western and eastern parts of Grobogan Regency and, as such, the farmers employed different adaptation strategies respective to their locations. In West Grobogan, focus was put on managing farmland with irrigation sourced from the Glapan dam. Meanwhile, in East Grobogan, rainfed agriculture, particularly for corn and soybean commodities, was customary. Analysis of the exploratory research suggested that 2 adaptation strategies are implemented by the farmers. First, the farmers commonly migrate and seek supplementary jobs to ensure income stability. Second, the farmers use planting techniques and seeds with superior quality and short harvest periods, which they invented.